Faktor determinan hipertensi pada wanita usia produktif dengan hipertensi di Kota Semarang - Hendriyani, Heni; Isnawati, Muflihah; Rahma, Sofi Aulia (Jurnal Gizi Klinik Indonesia, 2024)
Determinant factors among hypertensive productive-age women in SemarangBackground: Hypertension is a significant risk factor for developing cardiovascular disease, stroke, and kidney disease. The 2018 Basic Health Research results showed that hypertension in Indonesia reached 34.11%, and in Central Java province, the prevalence was above the national rate of 37.57%. The prevalence of hypertension among women is higher than men, namely 40.17% and 34.83%, respectively.Objective: This study aims to analyze the determinants of hypertension among women of reproductive age with hypertension in the city of Semarang.Methods: This study used a cross-sectional design. Respondents were women of productive age 30-50 years who were on the list of hypertensive patients in five Public Health Centers chosen randomly from the list. Data was collected by questionnaire, food recall form, and anthropometric measurement. One hundred fifty respondents participated in the study. Data analysis includes univariate and bivariate. Results: Foods high in sodium most frequently consumed were seasonings, monosodium glutamate (MSG), crackers, and soy sauce. Intake of potassium, magnesium, vitamin C, folic acid, and fiber is still far below the RDA, 21%, 5.8%, 66.3%, 4.5%, and 18.8%, respectively. Sodium intake from only food apart from spices is 45% of the RDA. 64.7% of respondents have high blood pressure. There was a significant relationship between blood pressure status and attitudes (p=0.045), consumption patterns of high-sodium foods (p=0.005), and physical activity (p=0.040). Conclusion: Food consumption and physical activity affect the blood pressure status of hypertensive patients in productive-age women. Efforts are needed to increase intake of food sources of vitamins and minerals.